131. The Protective Role of Mucosal Interferons in Infants with Respiratory Syncytial Virus (RSV) Infection. (31st December 2020) - Taveras, Jeanette; Garcia-Maurino, Cristina; Moore-Clingenpeel, Melissa; Mertz, Sara; Peeples, Mark E; Ramilo, Octavio; Mejias, Asuncion
Abstract: Background: Despite the high burden associated with RSV infection in young children the factors that determine disease severity are not well understood. The objective of this study was to assess the association of mucosal cytokine profiles, RSV loads (VL) and RSV disease severity. Methods: Single-center, prospective study in previously healthy infants with mild (outpatients; OP), moderate (inpatient-IP; ward) or severe (IP-PICU) RSV infection. Mid-turbinate swabs were obtained to measure VL by PCR, and cytokine concentrations (conc.) using a 13-plex panel that included type I (IFN-α2), II (IFN-γ), and III (IFN-λ2/λ3) interferons (IFN), and inflammatory cytokines. Multivariable analyses were performed to identify factors predictive of disease severity. Results: From 2014 to 2019 we enrolled 219 infants: 78 with mild RSV infection (OP; median [IQR] age, 6 [3.4–10.5] mo.), 101 with moderate disease (3.5 [1.3–8.3] mo.), and 40 with severe disease (2.3 [1.5–5.7] mo.). Duration of symptoms at enrollment was 4 (3–5) days and comparable between OP and IP, yet RSV VL in OP were significantly higher than in IP (8.1 [7.4–8.6] vs 7.4 [6.4–8.1] log10 copies/mL; p< 0.01) with no differences between ward and PICU infants. Median conc. of IFN-α2, IFN-γ, and IFN-λ2/λ3 were significantly higher in OP vs IP irrespective of hospitalization unit (Table 1). IP-10 conc. were also higher in OP and in ward patients vs PICU patients (p< 0.0001) and were independently associated with lower odds of supplemental O2 needs (OR, 95% CI: 0.4 [0.22–0.69]; p< 0.01) and PICU admission (0.4 [0.23–0.67]; p=0.001). In addition, higher IFN-λ2/λ3 conc. were nearly associated with lower odds of prolonged O2 use (OR: 0.35 [0.11–1.07]; p=0.07), and prolonged hospitalization (OR: 0.42 [0.16–1.03]; p=0.06). Conclusion: Infants with mild RSV infection had higher RSV VL and higher conc. of IP-10 and type-I, III IFN than those hospitalized with severe disease. These findings suggest that IP-10 and mucosal IFNs are associated with protection against severe RSV disease and could be used as biomarkers for patient stratification in the clinical setting. Disclosures: Octavio Ramilo, MD, Bill & Melinda Gates Foundation (Grant/Research Support)Janssen (Grant/Research Support, Advisor or Review Panel member)Medimmune (Grant/Research Support)Merck (Advisor or Review Panel member)NIH/NIAID (Grant/Research Support)Pfizer (Consultant, Advisor or Review Panel member)Sanofi/Medimmune (Consultant, Advisor or Review Panel member) Asuncion Mejias, MD, PhD, MsCS, Janssen (Grant/Research Support, Advisor or Review Panel member)Merck (Advisor or Review Panel member)Roche (Advisor or Review Panel member)